The existence of Dayah Salafiyah in the Development of Islamic Education in the era of globalization - Rahman, Mulia; Syahminan (Pascasarjana Universitas KH. Abdul Chalim, 2024)
For Dayah Salafiyah is a traditional Islamic educational institution that has an important role in maintaining and developing Islamic scientific heritage in Indonesia. This research aims to analyze the existence of Dayah Salafiyah in the context of the development of Islamic education in the era of globalization. The method used in this research is a qualitative approach with data collection techniques through interviews, observation, and literature study. The research results show that Dayah Salafiyah continues to exist and adapt to global challenges through various educational innovations without abandoning its traditional values. Dayah Salafiyah has integrated information technology into the learning process, developed a curriculum that is responsive to contemporary issues, and strengthened networks with other Islamic educational institutions, both at home and abroad. Despite facing various challenges, such as modernization and global cultural influences, Dayah Salafiyah has succeeded in maintaining its identity as an influential centre for Islamic education and preaching. This research concludes that the existence of Dayah Salafiyah in the development of Islamic education in the era of globalization not only shows adaptability but also a significant contribution to forming a strong Islamic character and understanding among Muslims. The recommendations of this research include the need for government and community support in facilitating the development of Dayah Salafiyah so that it can continue to make a positive contribution to Islamic education in Indonesia.